Multicentric evaluation of a second generation assay to detect antiviral citrullinated peptide antibodies: a collaborative study by the Forum Interdisciplinare per la Ricerca nelle Malattie Autoimmuni. Issue 12 (30th September 2011) - Bizzaro, N; Allegri, F; Alpini, C; Doria, A; Gerli, R; Lotzniker, M; Mathieu, A; Morozzi, G; Bellisai, F; Riccieri, V; Tampoia, M; Migliorini, P
Abstract : Aims: A novel immunoenzymatic assay using viral citrullinated peptides derived from Epstein–Barr virus-encoded proteins (viral citrullinated peptide 2 (VCP2)) has been developed and evaluated by means of a multicentre collaborative study. Methods: Three hundred nine sera from patients with established rheumatoid arthritis (RA), 36 with early arthritis, 12 with juvenile arthritis and 453 controls were tested for VCP2 and cyclic citrullinated peptide (CCP) antibodies. Results: The VCP2 assay showed 78.3% sensitivity and 97.1% specificity. VCP2 and CCP had a high concordance rate in patients with RA (88%) and controls (97%). However, 36 RA sera were positive in the CCP assay but negative on VCP2, and two RA sera reacted only on VCP2. Conclusions: The new VCP2 assay is endowed with high sensitivity and specificity. VCP2-positive RA sera are mostly but not completely contained in the CCP-positive population. Studies are in progress to establish whether the VCP2 assay can detect clinically distinct subsets of patients with RA.